2015
DOI: 10.1002/chem.201500023
|View full text |Cite
|
Sign up to set email alerts
|

Rational Topological Design for Fluorescence Enhancement upon Aggregation of Distyrylfuran Derivatives

Abstract: A series of 2,5-distyrylfuran derivatives bearing pentafluorophenyl- and cyanovinyl units have been synthesized for aggregation-induced emission (AIE). The effect of the type and extent of the supramolecular connections on the AIE of the furan derivatives were examined and correlated with their X-ray crystal structures. It was found that the simultaneous presence of cyano and perfluorophenyl units strongly enhances the fluorescence upon aggregation. Single-crystal X-ray diffraction analysis confirmed that CH⋅… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…As shown in Figure , and with planar structures exhibit ACQ properties for the strong π–π stacking interactions. Upon the incorporation of CN unit, the opposite AIE activities of the resultant molecules ( 25 and 26 ) are apparent, mainly due to the slightly distorted configurations with the cyano groups twisted from the plane (defined by the furan ring) . Meanwhile, in the aggregated state, the intermolecular CN⋯Ar F and CF⋯Ar F interactions and hydrogen bonds rigidify the configuration largely, directly contributing to the observed AIE phenomena.…”
Section: The Aggregation‐induced Emission Luminogens (Aiegens)mentioning
confidence: 99%
“…As shown in Figure , and with planar structures exhibit ACQ properties for the strong π–π stacking interactions. Upon the incorporation of CN unit, the opposite AIE activities of the resultant molecules ( 25 and 26 ) are apparent, mainly due to the slightly distorted configurations with the cyano groups twisted from the plane (defined by the furan ring) . Meanwhile, in the aggregated state, the intermolecular CN⋯Ar F and CF⋯Ar F interactions and hydrogen bonds rigidify the configuration largely, directly contributing to the observed AIE phenomena.…”
Section: The Aggregation‐induced Emission Luminogens (Aiegens)mentioning
confidence: 99%
“…The emission enhancement modes have principally been from aromatic stacking or weak binding of an analyte . Although it was recently demonstrated that supramolecular contacts that drive crystallization in the solid state can be used for AIE enhancement, only a limited number of examples have used such contacts for enhancing the fluorescence of azomethines. These have relied on the imine nitrogen to promote intermolecular =N⋅⋅⋅HS− and =N⋅⋅⋅HC− bonds in addition to intramolecular =N⋅⋅⋅HO− supramolecular contacts.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption and emission of F1 in dilute solution and when aggregated were subsequently evaluated. 33 The nitrile group therefore quenches the fluorescence in solution with the extent of deactivation contingent on the number of nitrile (Fig. As shown in Figure 4, the absorption spectrum of F1 in homogenous THF solution shows a non-structured absorption band at 395 nm.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…As shown in Figure 4, the absorption spectrum of F1 in homogenous THF solution shows a non-structured absorption band at 395 nm. 33 In solution, the fluorescence quantum yield (fl) decreased ca. 33 Water was added to THF solutions to aggregate FI and evaluate the resulting change in emission intensity and absorption.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
See 1 more Smart Citation